Mevduat sigorta sistemleri ve Azerbaycan uygulaması - Ahmadov, Tural (My University, 2009)
In the current period of globalization, countries’ economic integration into the world markets, free access of currencies into markets, entrance of foreign capital to economies resulted in easy reflection of any possible world-wide crisis on country economies. Such a situation also affected banks that play important role in the economy. Deposit insurance has been considered one of the most urgent methods to prevent savers’ “escape” from banks in times of banking crises. In this thesis, through the analysis of features, history, advantages and disadvantages of deposit insurance systems and examination of world-wide applied deposit insurance systems, proposals were made on the activities of newly founded deposit insurance fund of Azerbaijan. Banking System, Deposit Insurance, Risk Based Premiums

Yaşadığımız küreselleşme sürecinde ülke ekonomilerinin dünya piyasalarına açılması, piyasalara dövizin serbest bir şekilde girebilmesi, ülke ekonomilerine yabancı sermayenin girmesi dünya çapında oluşacak her hangi bir krizin kolay bir şekilde ülke ekonomilerine yansıması ile sonuçlanmıştır. Bu durum ekonomide önemli yer alan bankaları da etkilemiştir. Bankacılık krizleri zamanında tasarruf sahiplerinin bankalardan “kaçışlarını” önlemek için mevduat sigortası, en güncel yöntemlerden biri olarak görülmüştür. Bu çalışmada mevduat sigorta sisteminin özellikleri, tarihçesi, olumlu ve olumsuz tarafları ve dünyada uygulanan mevduat sigorta sistemleri incelenerek, Azerbaycan’da yeni kurulmuş olan mevduat sigorta fonunun faaliyeti ile ilgili önerilerde bulunulmuştur. Bankacılık Sistemi, Mevduat Sigortası, Riske Dayalı Prim Sistemi
Keywords: Bankacılık Sistemi; Mevduat Sigortası; Riske Dayalı Prim Sistemi